2018
DOI: 10.15625/2525-2518/55/4c/12141
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Green Space on the Land Surface Temperature in Hue City

Abstract: This paper presents the analysis of the effect of urban green space types on land surface temperature in Hue city. Data are collected with temperature monitoring results from each green space type and the interpretation of surface temperature based on Landsat 8 satellite image data to determine temperatures at different times of the year. Results showed that there was a significant correlation between types of urban green space and the surface temperature. Types of green space with a large area and vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the rise in population growth and tourism in Hue have caused deterioration of green spaces (Dinh & Pham, 2021 ), which is evident from NDVI and LST maps derived from the present study. A considerable reduction in LST patterns (1.6 °C during the day time) was reported from Hue from greenish areas of the city compared to the built-up areas (Nguyen, 2017 ). In addition, a recent study (Le Phuc et al, 2022 ) observed that a large number of waterbodies (river channels, lakes) in Hue city has some cooling effects and reduce the extend of UHI.…”
Section: Resultsmentioning
confidence: 98%
“…However, the rise in population growth and tourism in Hue have caused deterioration of green spaces (Dinh & Pham, 2021 ), which is evident from NDVI and LST maps derived from the present study. A considerable reduction in LST patterns (1.6 °C during the day time) was reported from Hue from greenish areas of the city compared to the built-up areas (Nguyen, 2017 ). In addition, a recent study (Le Phuc et al, 2022 ) observed that a large number of waterbodies (river channels, lakes) in Hue city has some cooling effects and reduce the extend of UHI.…”
Section: Resultsmentioning
confidence: 98%